Practice - Muehlberger, Ellen (Cambridge : Cambridge University Press, 2017)
The Cambridge Edition of Early Christian Writings provides definitive anthology of early Christian texts, from c.100 to 650 CE. Its six volumes reflect the cultural, intellectual and linguistic diversity of early Christianity and are organized thematically on the topics of God, practice, Christ, community, reading and creation. The series expands the pool of source material to include not only Greek and Latin writings, but also Syriac and Coptic texts. Additionally, the series rejects a theologically normative view by juxtaposing texts that were important in antiquity but later deemed'heretical', with orthodox texts. The translations are accompanied by introductions, notes, suggestions for further reading and scriptural indices. The second volume is focused on the topic of practice, including texts on education, advice, forming communities and instructing congregations. It will be an invaluable resource for students, academic researchers in early Christian studies, history of Christianity, theology, religious studies and late antique Roman history.
Title from publisher's bibliographic system (viewed on 24 Oct 2017).
Keywords: Theology, Practical -- Early works to 1800.; Theology -- Early works to 1800.; Christian literature, Early